EFEKTIVITAS KOMBINASI ASAM AMINO DAN TIAMIN (VITAMIN B1) TERHADAP PRODUKTIVITAS TANAMAN MELON BUDIDAYA HIDROPONIK - Ni'mawati Sakinah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
Proper nutrition will help increase productivity, on the other hand, an imbalance of nutrients can cause damage to plants. Hydroponic cultivation is expected to play a role in saving the use of nutrients more effectively. The combination of amino acids and vitamin B1 was given at different concentrations (0, 10, 20, and 30 mL/L) respectively. Measurements included plant height (cm), weight (gram), diameter (mm), and fruit flesh thickness (mm) as well as the total sugar content (Brix). Results showed that increasing the concentration did not significantly affect the response. The results of the LSD test showed that the addition of amino acid and vitamin B1 at doses of 10 mL/L was significantly different for the fruit diameter, explaining that increasing the dose of nutrients does not always have the best impact. Thus, the addition of a combination of amino acids and vitamin B1 for melon cultivation can be given at it lowest dose (10 mL/L).